Global representation of threatened amphibians ex situ is bolstered by non‐traditional institutions, but gaps remain. (18th August 2016) - Biega, A.; Greenberg, D. A.; Mooers, A. O.; Jones, O. R.; Martin, T. E.
Abstract: Ambitious global conservation targets have been set to manage increasing threats to amphibians. Ex situ institutions (broadly, 'zoos') are playing an expanding role in meeting these targets. Here, we examine the extent to which zoos house species representing the greatest overall conservation priority by testing how eight variables relating to extinction risk – International Union for the Conservation of Nature status, habitat specialization, obligate stream breeding, geographic range size, body size and island, high‐altitude and tropical endemism – vary between amphibian species held in zoos and their close relatives not held in zoos. Based on 253 species found in zoos that could be confidently paired with close relatives not in zoos, and in contrast to reported patterns for birds and mammals, we find that amphibians currently held in zoos are equally as threatened as their close relatives not found in zoos. This result is entirely driven by the inclusion of data on species holdings from Amphibian Ark (AArk), an organization that helps to coordinate conservation activities in many 'non‐traditional' institutions, as well as in 'traditional' commercial zoos. Such networks of small non‐traditional institutions thus make meaningful contributions to ex situ conservation, and the establishment of other taxa‐specific organizations modelled on AArk might be considered. That said, our results indicate that the ex situ network is still not prioritizing range‐restricted habitat specialists, species that possess greater overall extinction risk in the near future. We strongly encourage zoos to continue increasing their holdings of amphibian species, but to pay greater attention to these species of particular conservation concern. Abstract : We provide an analysis of amphibian ex‐situ holdings by testing how eight ecological and biogeographical variables relating to extinction risk vary between amphibian species held in zoos and their close relatives not held in zoos. We find that species held in zoos are equally as threatened as their close relatives not found in zoos but that range and habitat‐restricted species remain under‐represented ex‐situ . We highlight that the taxon specific conservation organization, Amphibian Ark, and non‐traditional zoos are having an important effect on the representation of threatened species held ex‐situ but also warn that species most at risk of short‐term extinction (range‐restricted specialists) require greater attention from the ex‐situ conservation community.